An innovative Web 2.0-Based collaborative learning framework: activities for the initial development of social negotiation competencies - Ataie, Farib; Shah, Asadullah; Imtiaz Ali, Najma (Science Publishing Corporation Inc, 2018)
This research aims to present a Facebook-based collaborative learning (CL) framework that supports initial development of social nego-tiation and debate competencies. This framework has implications for the International Debate Education Association (IDEA, 2018) that aims to promote the opportunity to debate, breaking down barriers of location, race and class while extending the boundaries of online-learning. The guidelines for CL and social negotiation in this study are based on social constructivist theory with the ethical system that value safe and structured environment for debate and negotiation. The integration of Facebook as an information and communication technology (IICT) provides conditions of CL and social negotiation, multiple modes and methods of learning and multiple perspectives, to achieve learning goals. This practical framework under the guidelines of design science research methodology (DSRM) motivates learners to actively engage in the CL and social negotiation processes with empathy, self- control, endurance and reasoning to develop critical thinking and awareness. This study will contribute to the World Universities Debating Championship (WUDC) that aims to com-plement communication skills of students with a culture of research and critical thinking. Experts reviewed and confirmed the validity of the framework. Three successive iterations working with Facebook members and experts in informal learning were conducted to demon-strate and validate how learners started developing social negotiation and debate competencies.